Toxicity of sulfate and chloride to early life stages of wild rice (Zizania palustris). (29th October 2014) - Fort, Douglas J.; Mathis, Michael B.; Walker, Rachel; Tuominen, Lindsey K.; Hansel, Mike; Hall, Scott; Richards, Robin; Grattan, S.R.; Anderson, Kurt
Abstract Despite the importance of wild rice (Zizania palustris) in the Great Lakes region of North America, its sensitivity to sulfate is not well understood. A 21‐d hydroponic experiment was performed to determine the toxicity of sulfate to wild rice seeds and seedlings. Effects of 6 sulfate concentrations ranging from 10 mg/L to 5000 mg/L and of chloride salts at equivalent conductivity were evaluated to determine whether adverse effects were attributable to sulfate or to conductivity‐related stress. Sulfate treatment decreased root length, shoot length, and leaf number, and increased phytotoxic effects at concentrations of 5000 mg/L relative to a 50 mg/L control. The time to 30% mesocotyl emergence decreased at 2500 mg/L sulfate, indicating a potential stimulatory effect. Sulfate exposures of ≤5000 mg/L had no effect on 5 additional end points. Multiple regression analysis indicated that most observed changes could be attributed to conductivity‐related stress rather than sulfate per se, with the exception of shoot length and leaf number. Chloride was more toxic than sulfate, as determined by root length and phytotoxicity. In summary, sulfate concentrations below 5000 mg/L did not adversely affect early–life stage wild rice during a 21‐d period, and effects at 5000 mg/L sulfate were attributable to conductivity‐related stress rather than sulfate toxicity in 2 of 4 end points. Environ Toxicol Chem 2014;33:2802–2809. © 2014 SETAC